Pengaruh Penerapan Model Blended Learning Terhadap Hasil Belajar Peserta Didik Materi Sistem Ekskresi - Maisarah, Indah; Azis, Andi Asmawati; Pagarra, Halifah (Biology Teaching and Learning, 2022)
Abstract. This study aims to find outthe learning outcomes of learners who are taught with Blended learning, to find out the influence of blended learning model on the learning outcomes of learners pateri excretion system in MA DDI Kanang and to find out the improvement of learning outcomes of learners of excretion system materials in MA DDI Kanang. This research is a pseudo experimental research (Quasy experimen t) using Pretest Posttest Control Group Design. The sample of the study was selected randomly (random sampling) so thattwo classes were obtained, namely class XI MIPA 2 as an experimental class with blended learning model and XI MIPA 1 as a control class using direct instruction learning model. Data collection techniques used through tests or evaluations. The collected data is analyzed in descriptive statistics and inferential statistics. The results of descriptive statistical analysis showed thatthe learning that was taught by blended learning model was in the category of excellent and good while in the control group that was taught with direct instruction was in the category of excellent, good and sufficient. The data obtained was also analyzed by N-Gain to determine the improvement of learners' learning outcomes and obtained learning outcomes of learners in high categories and classes taught by direct instruction were in the medium category. The results of inference analysis showed that there is an influence of Blended Learning model on the learning outcomes of learners of excretion system material in MA DDI Kanang.Keywords: blended learning, direct instruction, learning outcomes